Socialization on Improving English Language Skills through TOEFL for Grade 12 Students of SMK Swasta HKBP Pematang Siantar - Tamba, Dian Winda; Pardede, Ros Meylani Putri; Lubis, Hotnida Teresia; Gea, Ephy Cryday Yanti; Siahaan, Renita Clara; Herman, Herman; Purba, Anita; Tannuary, Arwin (Indra Institute Research & Publication, 2023)
This socialization activity aims to introduce and provide knowledge and insight to students at the SMK Swasta HKBP Pematang Siantar about the TOEFL test. The socialization activity regarding the introduction of TOEFL to vocational school students, was held on December 5, 2023. Participants in this socialization activity were 12 grade vocational school students totaling 20 people. Participants gain new knowledge about the TOEFL test. There were three phases in conducting this socialization, namely preparation, implementation and evaluation. The results obtained from this socialization activity are, they know and understand what the TOEFL test is, types of questions in the TOEFL test, number of questions tested in the TOEFL test, duration and time for completing TOEFL questions, tips & tricks for studying TOEFL and also the importance of TOEFL test. This socialization can also increase student's motivation to study English more seriously. They can view the TOEFL exam as a challenge to overcome and as a first step towards success in their future academic and professional careers. From the results above it can be concluded that this activity gave a positive impact for the students in the future